The global sanitary revolution in historical perspective - Daniel Gallardo-Albarrán (European Historical Economics Society (EHES), 2024)
This survey sheds light on the causes and consequences of the global sanitary revolution that resulted in the spread of waterworks and sewerage projects since the middle of the 19th century, by drawing on research from the fields of economic history, economics and history. I begin with a discussion of the construction of these infrastructures during the period 1850-1940 showing that their spread was relatively similar in major urban cities across the globe, while diffusion within countries and cities themselves was markedly unequal. Second, I review research looking at the mortality impact of access to clean water and sanitation. These account for ca. 10-30 percent of declines in infant mortality and in industrial settings their joint effect explains between 20 and 25 percent of the fall in infant and overall mortality. Lastly, I examine the drivers of the sanitary revolution with a new framework that distinguishes between proximate factors (e.g. physical capital) and ultimate factors (e.g. institutions). I argue that the state of knowledge in this literature is insufficient to explain between- and within-country differences in access to sanitary services and that more attention should be devoted to the interaction of political factors with economic, cultural and biogeographic contexts.
Keywords: I18; N30; N90; L95; 330; waterworks; sanitation; mortality; political economy; cities